2013
DOI: 10.1111/jfb.12190
|View full text |Cite
|
Sign up to set email alerts
|

Stocks and seasonal migrations of the flounder Xystreurys rasile as indicated by its parasites

Abstract: The aims of this study were (1) to compare the structure and composition of parasite assemblages of the flounder Xystreurys rasile in two regions of the Argentine Sea in order to evaluate the hypothesis for the existence of different stocks, and (2) to test the hypothesis for X. rasile migration from the Argentine-Uruguayan Common Fishing Zone (AUCFZ) towards more southern waters during spring. Parasitological evidence shows that at least two stocks of X. rasile inhabit the coastal and shelf waters of the nort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 45 publications
3
6
0
Order By: Relevance
“…The presence of a single stock of C. guatucupa in southern Uruguay and northern Buenos Aires province, as demonstrated by parasites (Timi et al 2005), agreed with a previous study by Díaz de Astarloa and Bolasina (1992) based on meristic and morphometric comparisons of hosts. In a similar way, compatible results between parasitological evidence and those derived from other methodologies have been obtained in stock studies of anchovies, hakes and flounders (Timi, 2003; Sardella and Timi, 2004; Alarcos and Timi, 2013).…”
Section: Validation Of the Methodology: Strengths And Weaknessessupporting
confidence: 77%
See 1 more Smart Citation
“…The presence of a single stock of C. guatucupa in southern Uruguay and northern Buenos Aires province, as demonstrated by parasites (Timi et al 2005), agreed with a previous study by Díaz de Astarloa and Bolasina (1992) based on meristic and morphometric comparisons of hosts. In a similar way, compatible results between parasitological evidence and those derived from other methodologies have been obtained in stock studies of anchovies, hakes and flounders (Timi, 2003; Sardella and Timi, 2004; Alarcos and Timi, 2013).…”
Section: Validation Of the Methodology: Strengths And Weaknessessupporting
confidence: 77%
“…Alarcos and Timi (2013), based also on the lack of differences between the parasite communities of samples of Xystreurys rasile , corroborated the seasonal migration of this species along north Argentine coasts suggested by previous ichthyological studies.…”
Section: Current Status Of the Use Of Parasites As Biological Tags Insupporting
confidence: 74%
“…There are studies that indicate segregation of feeding area migratory behaviour in other fish species. Alarcos and Timi (2013) showed different populations of flounders (Xystreurys rasile) habiting at least 2 different feeding areas in Argentine Sea and Aranda et al (2013) showed that Atlantic Bluefin tuna (Thunnus thynnus) mainly feed in the North Atlantic but minor proportion of the population feed in the Mediterranean. indicates salmon being distributed uniformly across all three feeding areas before ascending the river to spawn; strong connectivity (value of 0) indicates all individuals occupying only one feeding area.…”
Section: Figurementioning
confidence: 99%
“… Xystreurys rasile ( Actinopterygii : Paralichthyidae ); marine; body cavity, mesentery; metacestode; WTSA ; Argentina, Brazil ( Menoret and Ivanov 2009b ; Alarcos and Timi 2012 , 2013 ; Fonseca et al 2012 ).…”
Section: Parasite-host Listmentioning
confidence: 99%
“… Xystreurys rasile ( Actinopterygii : Paralichthyidae ); marine; intestine, mesentery; metacestode; WTSA ; Argentina ( Alarcos and Timi 2013 ).…”
Section: Parasite-host Listmentioning
confidence: 99%